2019
DOI: 10.3390/cells8050442
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Raf Kinase Inhibitor Protein (RKIP) in Lung Cancer: Behind RTK Signaling

Abstract: Lung cancer is the most deadly neoplasm with the highest incidence in both genders, with non-small cell lung cancer (NSCLC) being the most frequent subtype. Somatic mutations within the tyrosine kinase domain of the epidermal growth factor receptor (EGFR) gene are key drivers of NSCLC progression, with EGFR inhibitors being particularly beneficial for patients carrying the so-called “EGFR-sensitizing mutations”. However, patients eventually acquire resistance to these EGFR inhibitors, and a better knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 121 publications
(200 reference statements)
1
20
0
Order By: Relevance
“…This suggested that RKIP may not have a fundamental role in the primary tumour, but instead has great importance as a metastasis suppressor. In accordance, loss or reduction of RKIP expression is associated with malignancy and poor prognosis in several tumour types, as reported by our [16][17][18][19][20][21][22] and other groups [4,5,18,[23][24][25][26]. Biologically, RKIP is a multifunctional protein in carcinogenesis, regulating cellular growth [27,28], motility [29,30], epithelial-to-mesenchymal transition (EMT) [31] and invasion [32].…”
Section: Introductionsupporting
confidence: 70%
“…This suggested that RKIP may not have a fundamental role in the primary tumour, but instead has great importance as a metastasis suppressor. In accordance, loss or reduction of RKIP expression is associated with malignancy and poor prognosis in several tumour types, as reported by our [16][17][18][19][20][21][22] and other groups [4,5,18,[23][24][25][26]. Biologically, RKIP is a multifunctional protein in carcinogenesis, regulating cellular growth [27,28], motility [29,30], epithelial-to-mesenchymal transition (EMT) [31] and invasion [32].…”
Section: Introductionsupporting
confidence: 70%
“…Raf kinase inhibitor protein (RKIP) is a well-known suppressor in carcinogenesis and malignant progression 18 . Downregulation of RKIP has been observed in various cancers such as prostate cancer 19 , breast cancer 20 , lung cancer 21 , gastric cancer 22 , esophageal squamous cell carcinoma 23 , and colorectal cancer 24 . Reduction of RKIP is almost involved in promotion of each malignant characteristics, especially for metastasis and therapy resistance, by activating oncogenic regulators or signaling axes like NF-κB 25 , YY1 26 , STAT3 27 , MAPK 28 , and AKT 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Since these proteins are closely related to senescence processes [ 26 , 27 , 28 ], we decided to evaluate them in appendiceal NENs, and complement the analysis with the evaluation of an anti-apoptotic protein Bcl-2. We also evaluated RKIP, a protein that has been associated with a metastasis suppressive role in various neoplasms, namely gastrointestinal stromal tumors, breast cancer, prostate, and many others [ 29 , 30 , 31 , 32 , 33 ]. Contrary to the GCA [ 16 ], in appendiceal NENs of our series, p16 was expressed in the majority of the cases with moderate or strong staining.…”
Section: Discussionmentioning
confidence: 99%